Optical genome mapping in an atypical Pelizaeus-Merzbacher prenatal challenge - Rogac, Mihael; Kovanda, Anja; Lovrečić, Luca; Peterlin, Borut (Frontiers in Genetics, 2023)
Pathogenic genetic variants represent a challenge in prenatal counseling, especially when clinical presentation in familial carriers is atypical. We describe a prenatal case involving a microarray-detected duplication of PLP1 which causes X-linked Pelizaeus-Merzbacher disease, a progressive hypomyelinating leukodystrophy. Because of atypical clinical presentation in an older male child, the duplication was examined using a novel technology, optical genome mapping, and was found to be an inverted duplication, which has not been previously described. Simultaneously, segregation analysis identified another healthy adult male carrier of this unique structural rearrangement. The novel PLP1 structural variant was reclassified, and a healthy boy was delivered. In conclusion, we suggest that examining structural variants with novel methods is warranted especially in cases with atypical clinical presentation and may in these cases lead to improved prenatal and postnatal genetic counseling.